University students' adherence and vaccination attitudes during the COVID-19 pandemic: focusing on costs and benefits - Kulcar, Vanessa; Straganz, Christoph; Kreh, Alexander; Siller, Heidi; File, Norbert; Canazei, Markus; Bork-Hüffer, Tabea; Juen, Barbara (Applied psychology: health and well-being. Health and well-being, 2022)
Numerous measures were implemented to contain the COVID-19 pandemic. Adhering to these measures as well as getting vaccinated is associated with subjective costs and benefits. Since young people like university students largely feel less vulnerable to the virus, other costs and benefits than health might be more decisive for them. This article combines the results of a qualitative and a quantitative longitudinal study conducted with university students mainly living in Tyrol, Austria. The studies focused on the second wave of infections of the COVID-19 pandemic. Health concerns, altruistic concerns, worrying about the economic consequences of the measures and reactance played an important role for students in deciding what measures to follow and their vaccination attitudes. The effects were partially mediated by understanding the measures' necessity. Qualitative results enabled further insights into thought processes during these decisions and revealed additional aspects, such as concerns about mental health consequences. This research suggests that students make their decisions about adherence and vaccinations based on a variety of aspects that they weigh against each other. Understanding the individual assessments of costs and benefits is crucial to promote both adherence to the measures against the COVID-19 pandemic and vaccination readiness.
Gesehen am 14.04.2025
Online veröffentlicht: 3. November 2021